Uso de recursos humanos nas iniciativas de tecnologia da informação em um ambiente pervasivo de conhecimento digital - Guerra, Luiz Claudio (2022)
With the pervasive knowledge of technology in the corporate environment, the business areas of companies seek to directly implement solutions to achieve their digital goals. The implementation of these initiatives involves specialized human resources. If in the past these technology resources were centralized, with initiatives permeating the company, the possibility of synergies in the allocation of these resources is lost, quickly making them scarce and bringing inefficiency and waste to their use. This research aims to evaluate this context by using a qualitative multiple case studies approach. Conducted with ten managers from the business areas of six large companies in the manufacturing sector, it addresses aspects that influence the allocation of technology human resources for the development of technology initiatives in their business areas. Among these aspects, the scope, benefits, and responsibility of these initiatives were considered, as well as the required competencies and the origin of these resources. The results showed, in fact, initiatives being developed isolated and focused on meeting the strategic vision of the area. The technology resources used for development are their own and internal resources, and there is no resource sharing. If, on the one hand, this practice brings agility for the business areas, on the other hand, the non-sharing of competencies and human resources with other areas of the company motivates the creation of organizational silos, strategic misalignment in the application of technology, besides the lack of optimization in the use of these resources.